Pengaruh Skill Dan Budaya Kerja Terhadap Kinerja Karyawan Pada UD. Indokey - Giano Surya Pamungkas; Erwin Syahputra; Anita Sumelvia Dewi (Transformasi: Journal of Economics and Business Management, 2023)
Employee performance in a company that is not well managed can be one of the obstacles to company activities in achieving its goals. The purpose of this study is to explain the effect partially and simultaneously skills and work culture on employee performance. This type of research uses quantitative research. Source of data in this study using primary data and secondary data. The sample in this research is 40 employees of UD. Indokey uses a saturated sampling technique in which researchers use all UD employees. Indokey is a sample. The analysis technique used is validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, t test, F test, multiple linear regression analysis, and coefficient of determination test (R2) using the SPSS version 25 program. The results of this study are that partially the skill variable has a positive and significant effect on the performance of employees at UD. Indokey, partially the work culture variable has a positive and significant effect on the performance of employees at UD. Indokey and simultaneously stated that the variable skills and work culture have a significant effect on the performance of employees at UD. Indokey